Vice-Chancellors' Managerial Effectiveness in Edo and Kwara State Universities, Nigeria (Global Journal of Management and Business Research, 2019)
The quest for effective management of educational institutions in Nigeria required a concerted effort of all stakeholders in education system. Sequel to this, the paper examines the vice-chancellors managerial effectiveness of universities in Edo and Kwara states, Nigeria. The target population comprised all vice-chancellors in eleven (II) Universities in Edo and Kwara states (7 universities in Edo and 4 in Kwara states). Four universities were selected through a stratified random sampling technique in two states. Proportional sampling technique was used to select 2000 respondents comprising 1000 students and 1000 staff from four universities. Descriptive research design was adopted for the study. Two researchers design the questionnaires that were used to elicit information from the respondents. The first one tagged "Students' Perception of Level of Vice-chancellors' Managerial Effectiveness" Questionnaire (SPLVMEQ) was design to obtain the view of students on the subject matter. The second one entitled" Perception of members of Staff on Vice-chancellors' Managerial Effectiveness Questionnaire (PSLVMEQ) was designed to obtain the opinion of academics and non-academic staff of universities on their vicechancellors.